PENGARUH PENGEMBANGAN KARIR, MOTIVASI, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PADA PT. CIOMAS ADISATWA KOTA BENGKULU - Firnanda, Friska Fera; Subandrio, Subandrio (UM. Bengkulu, 2024)
This type of quantitative descriptive research, the object of this research is employees at PT. Ciomas Adisatwa Bengkulu City. The Sampling method uses a non probability technique, namely accidental Sampling. The number of respondents in this study were 40 people. Data collection method using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test. The results of this study can be concluded that career development (X1) has a positive effect on employe performance (Y), Motivation (X2) has a positive effect on employee performance(Y), Emotional intelligence (X3) has a positive effect on employee performance (Y), Then career development (X1), Motivation (X2), Emotional intelligence (X3) together have a positive and significant effect on employee performance (Y). Keywords: Career development, Motivation, Emotional intelligence, and employee performance.